Wasiat dalam Al-Qur’an dan Dinamika Pengaturannya di Indonesia: Kajian Tafsir Maudhū‘ī - Ulfa Safira Soliha; Sukiati; Fatimah (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
The regulation of wills (waṣiyyah) in Islamic law demonstrates a complex normative transformation that reflects the interaction between Qur’anic legal verses, juristic interpretation, and contemporary legal systems. Qur’anic provisions on wills, particularly in Q.S. al-Baqarah (180–182, 240) and Q.S. al-Mā’idah (106), initially positioned the will as a central mechanism for ensuring moral responsibility, social protection, and distributive justice prior to the formal codification of inheritance law. Subsequent developments in Islamic jurisprudence, however, introduced doctrinal limitations following the revelation of inheritance verses, reshaping the function of the will within Islamic legal thought. Through a thematic (tafsīr maudhū‘ī) analysis, this article demonstrates that Qur’anic regulations on wills form an integrated normative framework encompassing moral obligation, legal protection, corrective justice, and procedural accountability. When examined in the Indonesian context, the regulation of wills—particularly through the Compilation of Islamic Law—reveals a process of legal adaptation and reconstruction that responds to social realities while remaining anchored in Islamic legal principles. The expansion of concepts such as mandatory wills (waṣiyyah wājibah) illustrates how Islamic law operates dynamically within a plural legal system. This analysis underscores that wills function not merely as a residual legal instrument subordinate to inheritance law, but as a converging point between Qur’anic norms, juristic reasoning, and state regulation in contemporary Islamic family law.